2014
DOI: 10.1148/radiol.14130882
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Endofibrosis in Endurance Athletes: Angiographic Features and Classification

Abstract: This study assessed 180 patients (161 men, 19 women) with 195 symptomatic limbs (136 left-side limbs; P < .001). Angiography depicted 28 abnormalities in the CIA (27 stenoses, one dissection), 185 in the EIA (17 thromboses, 167 stenoses, one dissection), one in the common femoral artery (dissection), and 14 in the deep femoral artery (one thrombosis, 13 stenoses). CIA and EIA stenoses predominantly involved the distal and proximal third of the artery respectively. They were mild (CIA and EIA mean severity, 19%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…8e10 A consensus that exercise tests should be standardised was reached, which is an important step forward, and a description of this technique was recently published. 11,12 Patients should be exercised until they develop symptoms and the pressures (ankle and ABPI) should be measured if possible within 1 minute of exercise cessation with the patient in a supine position (and for this some units have adopted automatic systems to measure pressures simultaneously and rapidly in both lower limbs). Some institutions, which consider kinking to be a potential important cause of flow limitation, test the ankle pressures with the patient on a cycle ergometer in an upright position (with a correction being applied for vertical height difference) and with hips flexed.…”
Section: Discussionmentioning
confidence: 99%
“…8e10 A consensus that exercise tests should be standardised was reached, which is an important step forward, and a description of this technique was recently published. 11,12 Patients should be exercised until they develop symptoms and the pressures (ankle and ABPI) should be measured if possible within 1 minute of exercise cessation with the patient in a supine position (and for this some units have adopted automatic systems to measure pressures simultaneously and rapidly in both lower limbs). Some institutions, which consider kinking to be a potential important cause of flow limitation, test the ankle pressures with the patient on a cycle ergometer in an upright position (with a correction being applied for vertical height difference) and with hips flexed.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms include hardening of the thigh, cramps, and/or paralysis. Symptoms occur more commonly on the left side [ 9 ]. In 1995, Beck studied 164 cases of arterial endofibrosis and found that 50% of these patients complained of a paralyzing pain, a swollen thigh in 23%, both previous manifestations in 17%, typical claudication in 9%, and 1% had critical ischemia [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent finding of EIAE at DSA is smooth, long, and eccentric stenosis, with thrombosis and dissection present less frequently [1]. Although the external iliac artery is most frequently affected, the common iliac artery can be involved in approximately 15% of patients [32]. A benefit of arteriography, relative to other modalities, is that the pressure gradient across the narrowing can be measured at baseline as well as during various maneuvers, including following the administration of vasodilators [33].…”
Section: Us Intravascular Lower Extremitymentioning
confidence: 99%
“…A benefit of arteriography, relative to other modalities, is that the pressure gradient across the narrowing can be measured at baseline as well as during various maneuvers, including following the administration of vasodilators [33]. Acquiring images during hip flexion frequently reveals a kink in the iliac arteries at the site of stenosis [32].…”
Section: Us Intravascular Lower Extremitymentioning
confidence: 99%